The understanding of international tourism development - van der Wal , Marcus (Applied Studies in Agribusiness and Commerce, 2011)
Tourism is travel for recreational, leisure or business purposes. Tourism has become one of the major players in international commerce, and represents at the same time one of the main income sources for many developing countries. This growth goes hand in hand with an increasing diversification and competition among destinations (Unwto, 2010).Working and serving in this pumping industry means to understand and react to the needs of all these people moving around this “small” planet! Success is defined by those who understand these needs and fulfill them to the satisfaction. Unfortunately, our industry is rather slow and we can be characterized as reactive instead of innovative.We adapt too slow compared to other industries that define the needs of their costumers before the costumers actually calls for it!